Pea Seed (Pisum sativum L.) Extract Exhibits Cytotoxic Activity against T47D Cancer Cells - Chasani, Failasufia Maulida; Hidayati, Devi Nisa; Hartati, Indah (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Pea (Pisum sativum L.) contain flavonoids with potential anticancer activity against breast cancer cells. Yet, the influence of extraction methods and solvent choice on flavonoid yield and bioactivity remains insufficiently studied. This study evaluated the effect of solvent type and extraction method on the flavonoid content and cytotoxic activity of Pisum sativum L. seed extract on T47D breast cancer cells. Extraction was performed using reflux and infusion methods with 96% ethanol, 70% ethanol, and water solvents. Flavonoid content was determined using the AlCl₃ colorimetric test, while cytotoxic activity was tested using the MTT method. The results showed that the 96% ethanol extract had the highest flavonoid content (9.88 ± 0.05 mg QE/g), followed by 70% ethanol (5.91 ± 0.26 mg QE/g) and water extract (2.63 ± 0.06 mg QE/g). Cytotoxic activity was demonstrated by 96% and 70% ethanol extracts with IC₅₀ values of 147.12 ± 8.81 µg/mL and 90.59 ± 5.75 µg/mL, respectively, while the water extract was inactive. These findings confirm that solvent polarity plays an important role in optimizing flavonoid content and cytotoxic potential. However, high flavonoid content does not always correlate with cytotoxic effects, so a comprehensive approach is needed in the development of natural-based anticancer agents.